(untitled) (Altre Modernità, 2011)
The paper deals about two plays by the so called “fourth bard” of Polish literature, the modernist playwright Stanislaw Wyspianski (1869-1907). Best known for his drama The Wedding (1901), Wyspiański devoted his first theatrical work, an opera libretto published only after his death, to Daniel (1895). In this early work, the Biblical theme is developed according to the messianic virtues attributed to poetry by the main Polish romantic poet and playwright, Adam Mickiewicz. While writing about Daniel, Wyspiański was inspired by a Rembrandt’s painting, Belshazzar’s Feast (1635) preserved at the National Gallery in London. As a matter of fact, the biblical thread of Daniel’s prophetic dream about the subduing of Three Kings (Daniel 7: 24) was exploited by Wyspiański in order to allude to the political predicament of the Polish nation oppressed by the three parting powers: Prussia, Austria and Russia. The play was therefore edited by Austrian censorship and was staged for the first time only in 1927, once Poland had regained her independence: not on a Polish scene, though, but by the Krokewer Yidish Teater in Dawid Liebl’s yiddish translation. The second play partly centered on a biblical theme is Akropolis (1904), a monumental drama set in Cracow’s Pantheon, the Wawel cathedral. In the second act of the play, the characters of the tapestries hanging on the walls of the cathedral come to life. One of the tapestries portraits the story of Jacob (Genesis: 25-33). Wyspiański was very likely inspired by Raffaello’s fresco paintings in Eliodor’s room at the Vatican, and by Gerhard Hauptmann’s fragment Das Hirtenlied. The playwright closely follows the text of the Bible but for a few „apocryphical” insertions, the more relevant of which refer to Jacob’s struggle with the Angel. The Angel defies Jacob, founder of tribes”, claiming that he’ll thread „on the weak ones, in this graveyard of tribes”. Much has been debated on where the action of the drama should take place. Wyspiański himself thought about staging Akropolis in the cathedral on the Wawel hill, but the best known production of the play, performed by Jerzy Grotowski (1962), dispensed from the original setting. For Wyspiański, the cathedral on the Wawel hill, with her tombs, was the most significant achievement in Polish national history and culture, but for Grotowski the most meaningful event in the history of the whole humankind had taken place in Auschwitz extermination camp. Grotowski sees the setting of the play – using Wyspianski’s words - „in a graveyard of tribes”. This graveyard is not longer the peaceful and magnificent cathedral where the playwright used to stroll in search of inspiration, but a dramatically real one, the graveyard in which millions of human beings belonging to all nations have been buried after having completed the crematorium in which they and their companions will be burned. Grotowski has not altered Wyspiański’s lines, just changed the order of the scenes, so that Jacob’s struggle with the Angel could be at the centre of a play which could be reintepreted by the light shed on Auschwitz extermination machine by Tadeusz Borowski’s concentrationary short stories. The last line of the play comes from a caption imagined by Wyspiański for its monumental drama, but the old words have for the modern audience a tragic and complete new meaning: „they’re gone, spirals of smoke float in the air”.